Adult vascular dysfunction in foetal growth‐restricted guinea‐pigs is associated with a neonate‐adult switching in Nos3 DNA methylation. (11th July 2019) - Krause, Bernardo J.; Peñaloza, Estefanía; Candia, Alejandro; Cañas, Daniel; Hernández, Cherie; Arenas, German A.; Peralta‐Scholz, María José; Valenzuela, Rodrigo; García‐Herrera, Claudio; Herrera, Emilio A.
Abstract: Aim: Foetal growth restriction (FGR) is associated with endothelial dysfunction and cardiovascular diseases in adult subjects. Early vascular remodelling and epigenetic changes occurring on key endothelial genes might precede this altered vascular function. Further, it has been proposed that oxidative stress during development may determine some of these epigenetic modifications. To address this issue, we studied the in vivo and ex vivo vascular function and Nos3 promoter DNA methylation in arteries from eight‐month‐old guinea‐pig born from control, FGR‐treated and FGR‐NAC‐treated pregnancies. Methods: Femoral and carotid arteries in vivo vascular function were determined by Doppler, whilst ex vivo vascular function and biomechanical properties were assessed by wire myography. Levels of eNOS mRNA and site‐specific DNA methylation in Nos3 promoter in aorta endothelial cells (AEC) were determined by qPCR and pyrosequencing respectively. Results: FGR adult showed an increased femoral vascular resistance ( P < .05), stiffness ( P < .05) and arterial remodelling ( P < .01), along with an impaired NO‐mediated relaxation ( P < .001). These effects were prevented by maternal treatment with NAC. Endothelial‐NOS mRNA levels were decreased in FGR adult compared with control and FGR‐NAC ( P < .05), associated with increased DNA methylation levels ( P < .01). Comparison of Nos3 DNA methylation in AEC showed a differential methylation pattern between foetal and adult guinea‐pigs ( P < .05). Conclusion: Altogether, these data suggest that adult vascular dysfunction in the FGR does not result from early changes in Nos3 promoter DNA methylation, but from an altered vessel structure established during foetal development.